Reflectivity Modelling of All-Porous-Silicon Distributed Bragg Reflectors and Fabry-Perot Microcavities - Samuolienė, N.; Šatkovskis, E. (Nonlinear Analysis: Modelling and Control, 2005)
Herein, the problem of nanocrystaline silicon laser and its importance in microelectronics are discussed upon. The features of vertical Fabry-Perot microcavities made on the base of porous silicon are described. The responses of the reflectivity of the distributed reflection Bragg mirrors and Fabry-Perot microcavities were found using transfer matrixes method for this purpose. Inherent optical parameters of porous silicon, deposited by electrochemical etch, were used in the calculations. The calculation of the reflectivity of the distributed reflection Bragg mirrors with front active layer of nanostructural porous silicon had been examined. In the second part, the features of Fabry-Perot microcavities on variation of the number of layers of the front or rear mirrors are described. The impact of the thickness of the active nanocrystaline silicon spacer between two distributed reflection Bragg mirrors upon the spectra of optical reflectivity of Fabry-Perot microcavities in the wavelength range of 0.4–0.9 µm had been examined as well. The made conclusions are important for improvement of the thickness of the active porous silicon spacer in front of Bragg mirror and the features of Fabry-Perot microcavities.
Keywords: porous silicon; modelling; Fabry-Perot microcavity